Electrochemical Solid-State Electrolyte Reactors: Configurations, Applications, and Future Prospects - Weisong Li; Yanjie Zhai; Shanhe Gong; Yingying Zhou; Qing Xia; Jie Wu; Xiao Zhang (Nano-Micro Letters, 2025)
Highlights Solid-state electrolyte reactors are elucidated in terms of their distinctive electrochemical architecture to facilitate the efficient direct synthesis of fuels and chemicals without the need for traditional purification steps. The core components, variable configurations, and distinct electrochemical reaction mechanisms of different chambers are systematically summarized. Potential future application scenarios and advanced cell stack designs are pointed out.